The last Qur’an from al-Andalus? - Arias-Torres, Juan Pablo (Edinburgh University Press, 2022)
The aim of this paper is to improve upon the description of ms. 2 of the Escuela de Estudios Árabes de Granada, and to propose a new date based on the material analysis of the document carried out by Sonsoles González (2014), and our rereading and translation of its colophon. If one accepts our proposal, this would be the last Qur’an from the Iberian peninsula, copied as late as the late seventeenth or early eighteenth century, in the city of Córdoba. Moreover, this copy is heir to an Andalusi tradition stretching back to the theoretical treatises of Abū ʿAmr ʿUthmān al-Dānī, transmitted faithfully from generation to generation through the Andalusi, Mudejar and Morisco periods, down to the period of this manuscript. Lastly, the marginal notes with chapter numbers and Latin translations of the sura titles are clear evidence of its later use among Christian intellectual circles.
Keywords: Corán - Crítica textual; Corán - Manuscritos - Al-Andalus; Qur'anic manuscripts; Escuela de Estudios Árabes (Granada); Latin translations; Ms 2